A narrative review of the dichotomy between the social views of non-monogamy and the experiences of consensual non-monogamous people - Rodrigues, D. L. (2024)
Monogamy is deeply rooted in most Western societies, shaping how people construe and behave in romantic relationships. These normative views facilitate the emergence of negative perceptions and evaluations when people choose not to adhere to mononormativity. Even though people in consensual non-monogamous (CNM) relationships are targets of stigmatization, research shows a dichotomy between these negative views and the relational experiences of CNM people. Indeed, people in CNM and monogamous relationships have comparable relationship functioning and quality and struggle with similar relationship problems. One of the differences is that CNM relationships afford people to explore their sexuality and fulfill their needs with multiple partners, without agreed-upon extradyadic behavior being perceived as infidelity or having deleterious consequences to relationship maintenance. These positive experiences notwithstanding, CNM people are continuously pressured by mononormativity and stigmatization, increasing the risk of internalized CNM negativity and worse personal and relational outcomes. One possible way to counteract CNM stigmatization and improve the lives of CNM people is by changing discourses surrounding non-monogamy and improving acceptance, not only in professional settings but also in the general population. Another strategy is to understand how the relationship beliefs and scripts of younger generations can help promote more inclusive and diverse societies.